2011
DOI: 10.1074/jbc.m110.201087
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Regulation by C1q/TNF-related Protein-13 (CTRP13)

Abstract: Members of the C1q/TNF family play important and diverse roles in the immune, endocrine, skeletal, vascular, and sensory systems. Here, we identify and characterize CTRP13, a new and extremely conserved member of the C1q/TNF family. CTRP13 is preferentially expressed by adipose tissue and the brain in mice and predominantly by adipose tissue in humans. Within mouse adipose tissue, CTRP13 is largely expressed by cells of the stromal vascular compartment. Due to sexually dimorphic expression patterns, female mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 72 publications
4
74
2
Order By: Relevance
“…This difference remained significant even after adjustment for age, BMI and serum adiponectin for NAFLD and NAFLD+T2DM groups. Our result is inconsistent with observations reported by Peterson JM et al and Byerly MS et al They found that plasma level of CTRP13 decreased in in leptin-deficient mice [8,9]. This discrepancy may arise due to differences in sample type.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This difference remained significant even after adjustment for age, BMI and serum adiponectin for NAFLD and NAFLD+T2DM groups. Our result is inconsistent with observations reported by Peterson JM et al and Byerly MS et al They found that plasma level of CTRP13 decreased in in leptin-deficient mice [8,9]. This discrepancy may arise due to differences in sample type.…”
Section: Discussioncontrasting
confidence: 99%
“…According to the previous studies, AMPK function leads to beta-oxidation induction [21]. Since, AMPK can be induced by CTRP13 [8]; it seems that reduced CTRP13 serum levels have a negative effect on beta oxidation. However, molecular mechanistic studies are required to establish this concept.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, both adipolin and adiponectin are down-regulated in obese states. In contrast to adipolin and adiponectin, the expression of other members of this family in fat tissues is either increased or unchanged in obese states (25,26). For instance, a recent report showed that CTRP13 in fat tissue is up-regulated in obese states, but this factor stimulates glucose uptake in muscle and reduces hepatic glucose output in vitro, indicating a role in glucose homeostasis (25).…”
Section: Discussionmentioning
confidence: 99%